2017
DOI: 10.3748/wjg.v23.i7.1250
|View full text |Cite
|
Sign up to set email alerts
|

B2 adrenergic receptors and morphological changes of the enteric nervous system in colorectal adenocarcinoma

Abstract: AIMTo study the morphology of the enteric nervous system and the expression of beta-2 adrenergic (B2A) receptors in primary colorectal cancer.METHODSIn this study, we included forty-eight patients with primary colorectal cancer and nine patients for control tissue from the excision of a colonic segment for benign conditions. We determined the clinicopathological features and evaluated the immunohistochemical expression pattern of B2A receptors as well as the morphological changes of the enteric nervous system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 29 publications
(35 reference statements)
0
25
0
Order By: Relevance
“…Free plasma metanephrine and normetanephrine are metabolites of catecholamines, the latter being considered a hormone that is released into the blood, especially during periods of physical or emotional stress, depression, or anxiety, causing both psychological and endocrine changes [ 17 ]. These catecholamines produced from the precursor tyrosine can, on the one hand, alter the immune response and, on the other hand, promote several biological signaling pathways involved in tumor initiation, growth, and metastasis [ 16 , 17 , 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Free plasma metanephrine and normetanephrine are metabolites of catecholamines, the latter being considered a hormone that is released into the blood, especially during periods of physical or emotional stress, depression, or anxiety, causing both psychological and endocrine changes [ 17 ]. These catecholamines produced from the precursor tyrosine can, on the one hand, alter the immune response and, on the other hand, promote several biological signaling pathways involved in tumor initiation, growth, and metastasis [ 16 , 17 , 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the involvement of the sympathetic nervous system in the development and evolution of gastric cancer, the primary pathway is mediated by the action of neurotransmitters on β2-adrenergic receptors, activating an intracellular signaling cascade via adenylyl cyclase [ 18 , 19 ]. Studies have highlighted the impact of the main neurotransmitter of the sympathetic nervous system, norepinephrine, on vascular endothelial growth factor (VEGF) and matrix metalloproteinase 2/9 (MMP-2 and MMP-9) [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, more recent studies have compared obese children with non-obese ones and have shown a significant increase in the intima-media thickness in obese patients (21,22). At the same time, the reduction of the intima-media thickness measured at the carotid level in obese subjects after exercise and diet suggests a certain degree of reversibility of early changes in atherosclerosis (23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…It is difficult to assess whether the contribution of neurons to colorectal carcinogenesis is attributable to the extrinsic or intrinsic GI innervation. Even though some studies that investigated the structural changes of the ENS in CRC have validated previous findings that CRC is able to induce atrophy of the ENS [ 69 , 70 ], another study has demonstrated that neuronal innervation in the tumor area increases in higher grade tumors [ 71 ]. Due to this observation and the known prognostic value of PNI, different researchers studied the prognostic value of other neuronal (related) markers in CRC.…”
Section: Nervous System Innervation In Colorectal Cancermentioning
confidence: 96%
“…When activated by sympathetic signaling, they can promote metastasis in several cancer types [ 103 ]. Whereas β-adrenergic receptors are associated with tumor grade in CRC [ 71 ] and meta-analyses of β-blocker use showed improved survival rates in patients with various types of cancer (ovarian cancer, pancreatic cancer, and melanoma), no improved survival time was found for CRC patients [ 104 , 105 ]. Further understanding about the role of the intrinsic and extrinsic GI innervation in carcinogenesis is necessary before new therapeutic options can be revealed, because the research on the role of the nervous system in CRC is still in its infancy.…”
Section: Therapeutic Potentialmentioning
confidence: 99%